ORGANIZATION OF THE MANAGEMENT OF ENTERPRISE SALES ACTIVITIES - Ivanitskyi , І.; Ivanitskyi , Ю. (Bulletin of Lviv National Environmental University. Series "AIC Economics", 2024)
One of the conditions for the effective functioning of an enterprise is the organization of sales activities for the produced goods, aimed at satisfying consumer needs. The challenges of managing enterprises' sales activities in the current economic conditions and the search for optimal ways and strategies to enter sales markets lead to the formation of an organizational structure – a sales management system. The problem of organizing sales activities in the current conditions remains relevant and requires further research in developing ways to increase the efficiency of sales of domestic enterprises. Effective organization of sales management and timely implementation of progressive sales strategies can ensure stable market positions for an enterprise. The organizational structure of sales management in an enterprise is a combination of management and production units that organize and carry out a complex of sales operations to deliver finished products to consumers according to their requirements. The sales system of an enterprise can be considered one of the main subsystems of its functioning, directly impacting performance results. The main goal of the sales sphere is to satisfy consumer needs for goods and services, characterized by their volume and structure of realization. The sales system is one of the factors of product competitiveness. Accordingly, the enterprise needs to formulate a proper sales strategy. Therefore, an important direction in the research of sales activities is both the development and implementation of the strategy through the organization of sales activities. Sales should be regarded as a crucial factor in increasing the efficiency of an enterprise's activities. The orientation of sales activities towards meeting consumer demand requires improving processes of interaction with clients, considering the market situation, and enhancing the organizational support of the enterprise's sales processes.